Australian Longan industry strategic plan (RIRDC, 1998)
RIRDC funded the workshop as part of its new products R&D program, which aims to faciliate the developement of new industries based on plants or plant product that have commercial potential for Australia. Thisa strategic paln provides the basic for future investment decision by the RIRDC in the longan industry.